Role of Microfinance in Women Empowerment in Mathura District of Uttar Pradesh - Yadav, Satendra; Kumar, Yogesh; Dwivedi, Ram Kumar (AMC Indian Journal of Entrepreneurship, 2017)
Women have a very important role in the world. It is important that women contribute to their families and also to the society. Men and women should work together without any gender bias and should also contribute socially, economically, and politically without any gender imbalance. The main objectives of micro finance programme are to give attention to women for development. Through microfinance we can empower women by providing them financial assistance and allowing them to earn an independent income, contribute financially to their household and generate self employment. There are many factors that can affect the women empowerment i.e. abilities, environment, initiative, and status of women as a group. The present study empirically examined whether microcredit can promote empowerment of rural and urban women in Mathura District of Uttar Pradesh (U.P.) This study evaluated the impact of microcredit on women's empowerment in Mathura district of U.P. The findings of the study suggest that there are some factors that are having impact of microfinance on women empowerment and some are not having impact. The results indicate that microcredit strengthens womens' standing represented by their greater role in the household decision making process.